2009
DOI: 10.1590/s0074-02762009000500011
|View full text |Cite
|
Sign up to set email alerts
|

Blastocystis subtypes in irritable bowel syndrome and inflammatory bowel disease in Ankara, Turkey

Abstract: Blastocystis infection has been reported to be associated with irritable bowel syndrome (IBS)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
67
1
2

Year Published

2009
2009
2018
2018

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 118 publications
(78 citation statements)
references
References 25 publications
5
67
1
2
Order By: Relevance
“…In this study, the pathogenesis of B. hominis subtypes is not investigated but some differences in virulence between Blastocystis subtypes was shown (9,20,31,32). In many studies, pathogenic potential of subtype 3 has been reported (16,31,(33)(34)(35). Also, some investigations have demonstrated that other subtypes such as subtype 1 were associated with symptoms (20,31,34,36).…”
Section: Discussionmentioning
confidence: 85%
“…In this study, the pathogenesis of B. hominis subtypes is not investigated but some differences in virulence between Blastocystis subtypes was shown (9,20,31,32). In many studies, pathogenic potential of subtype 3 has been reported (16,31,(33)(34)(35). Also, some investigations have demonstrated that other subtypes such as subtype 1 were associated with symptoms (20,31,34,36).…”
Section: Discussionmentioning
confidence: 85%
“…In numerous other investigations there was no association between Blastocystis subtypes and gastrointestinal symptoms [31,51,52]. They identified ST3 as the most frequent subtype in both groups (symptomatic and asymptomatic), but did not observe a significant relationship between this subtype and gastrointestinal symptoms.…”
Section: Pathogenicity Of Blastocystis Sp Is a Relationship Possiblementioning
confidence: 85%
“…Numbers of female and male participants were 143 (62.2%) and 87 (37.8%), respectively. Distribution of the individuals according to the age groups was nine (3.9%) for age 7-19, 76 (33%) for age 20-39, 90 (39.1%) for age [40][41][42][43][44][45][46][47][48][49][50][51][52][53][54][55][56][57][58][59], and 55 (24%) for age 60 and above. A minority of the participants (24%) were university graduates; however, most of the individuals (91.7%) had middle or high socioeconomic status.…”
Section: Resultsmentioning
confidence: 99%
“…[6][7][8] In Turkey, the most predominant Blastocystis ST was documented as ST3, which was followed by ST1 and ST2. 12,50,51 In the European countries, distribution of the STs tended to be similar to Turkey, and in addition, ST4 was commonly observed. 8 On the contrary, ST5-ST9 were detected sporadically in humans.…”
Section: Discussionmentioning
confidence: 95%